2016
DOI: 10.1080/00288306.2015.1133664
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic ground motion modelling of the largestMw5.9 + aftershocks of the Canterbury 2010–2011 earthquake sequence

Abstract: The 2010-2011 Canterbury earthquake sequence includes the 22 February 2011 Christchurch aftershock (M w 6.2), the June 2011 M w 6.0 aftershock and the December 2011 magnitude (M L ) 5.8 and 6.0 aftershocks. These events caused widespread liquefaction, landslides and heavy building damage and collapse. To better understand the contributions of the source, path and site effects to these damaging ground motions, we compute broadband synthetic seismograms for the largest M w 5.9 + aftershocks of the 2010-2011 Cant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Holden and Kaiser (2016) used detailed source models combined with calibrated, region‐specific parameters to develop synthetic seismograms. Comparing the synthetic seismograms (corrected for site effects) with ground motion recordings for several CES events in the greater Canterbury region indicated that they capture key aspects of the ground motion, including PGA and spectral content (Holden & Kaiser, 2016). Given the generally high shear wave velocity of the basaltic materials at the study sites (Massey et al., 2017), we adopted free‐field ground motion parameters assuming rock free‐field site conditions (i.e., without site or topographic effects) to estimate ground shaking in the rock slopes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Holden and Kaiser (2016) used detailed source models combined with calibrated, region‐specific parameters to develop synthetic seismograms. Comparing the synthetic seismograms (corrected for site effects) with ground motion recordings for several CES events in the greater Canterbury region indicated that they capture key aspects of the ground motion, including PGA and spectral content (Holden & Kaiser, 2016). Given the generally high shear wave velocity of the basaltic materials at the study sites (Massey et al., 2017), we adopted free‐field ground motion parameters assuming rock free‐field site conditions (i.e., without site or topographic effects) to estimate ground shaking in the rock slopes.…”
Section: Methodsmentioning
confidence: 99%
“…Given the generally high shear wave velocity of the basaltic materials at the study sites (Massey et al., 2017), we adopted free‐field ground motion parameters assuming rock free‐field site conditions (i.e., without site or topographic effects) to estimate ground shaking in the rock slopes. Holden and Kaiser (2016) simulated key earthquakes from the CES, including events of 22 February, 16 April, 13 June, and 23 December 2011 and a later moderate‐intensity event on 14 February 2016. Debris was observed to have fallen from the sites' large slopes during each of these earthquakes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to new insights into the evolution of the complex earthquake sequence, John's work underpins ongoing efforts to forecast what might be expected to occur in future earthquakes in that area as the Canterbury earthquake sequence evolves. Holden & Kaiser (2016) undertake stochastic ground motion modelling of many of the largest aftershocks in the Canterbury sequence. To help constrain these models, they use detailed source information underpinned by John's geodetic work on the Canterbury sequence.…”
Section: Introductionmentioning
confidence: 99%